2016
DOI: 10.1080/10428194.2016.1260122
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activation of alternative nuclear factor kappa B pathway in canine diffuse large B-cell lymphoma contributes to tumor cell survival and is a target of new adjuvant therapies

Abstract: Activation of the classical nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB) pathway is a common molecular event observed in both human and canine diffuse large B-cell lymphoma (DLBCL). Although the oncogenic potential of the alternative NFκB pathway (ANFκBP) has also been recently identified in DLBCL, its precise role in tumor pathogenesis and potential as a treatment target is understudied. We hypothesized that up-regulation of the ANFκBP plays an important role in the proliferation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Two different comparative gene expression studies 2 , 3 demonstrated that cDLBCL shares similar features with its human counterpart, in particular highlighting the interplay among specific molecular pathways (i.e. NF-κB, PI3K/AKT, Notch and JAK/STAT), which may have potential therapeutic implications 2 , 4 . In addition, recurrent copy number variations were identified by array comparative genomic hybridization (aCGH) including gains in chr13, syntenic to the region in human chromosome 8 containing MYC oncogene, and chr31 5 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Two different comparative gene expression studies 2 , 3 demonstrated that cDLBCL shares similar features with its human counterpart, in particular highlighting the interplay among specific molecular pathways (i.e. NF-κB, PI3K/AKT, Notch and JAK/STAT), which may have potential therapeutic implications 2 , 4 . In addition, recurrent copy number variations were identified by array comparative genomic hybridization (aCGH) including gains in chr13, syntenic to the region in human chromosome 8 containing MYC oncogene, and chr31 5 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Many lymphoid malignancies, including human and canine DLBCL, have increased NF-kB signalling [ 3 , 79 , 80 ]. Recent molecular research has revealed that methylation of the CpG dinucleotide next to kB sites changes the regulatory activity of NF-kB [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular determinants for pevonedistat drug sensitivity may be beyond the scope of canonical NF‐κB signalling. Recent study showed that the alternative NF‐κB pathway (ANF‐κBP) is constitutively active in primary canine DLBCL samples, contributes to lymphoma cell survival and may serve as a therapeutic target . Thus, ANF‐κBP signalling status may also impact patient response to pevonedistat treatment.…”
Section: Discussionmentioning
confidence: 99%